Respuesta :
Answer:
Radius of Convergence: 2
Interval of Convergence: [-2, 2]
General Formulas and Concepts:
Pre-Algebra
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
- Left to Right
Equality Properties
- Multiplication Property of Equality
- Division Property of Equality
- Addition Property of Equality
- Subtraction Property of Equality
Algebra I
- Exponential Rule [Multiplying]: [tex]\displaystyle b^m \cdot b^n = b^{m + n}[/tex]
- Exponential Rule [Dividing]: [tex]\displaystyle \frac{b^m}{b^n} = b^{m - n}[/tex]
Calculus
Series Convergence Tests
- P-Series: [tex]\displaystyle \sum \limit_{n = 1}^\infty \frac{1}{n^p}[/tex]
- Direct Comparison Test (DCT)
- Alternating Series Test (AST)
- Ratio Test: [tex]\displaystyle \lim_{n \to \infty} \bigg| \frac{a_{n + 1}}{a_n} \bigg|[/tex]
Radius of Convergence (ROC)
- Ratio Test
- Interval bound
Interval of Convergence (IOC)
- Testing endpoints
Step-by-step explanation:
Step 1: Define
[tex]\displaystyle \sum \limit_{n = 1}^\infty \frac{x^n}{2^n(n + 1)^2}[/tex]
Step 2: Find ROC
Apply Ratio Test
- [Series] Set up [Ratio Test]: [tex]\displaystyle \lim_{n \to \infty} \bigg|\frac{x^{n + 1}}{2^{n + 1}(n + 2)^2} \cdot \frac{2^n(n + 1)^2}{x^n} \bigg|[/tex]
- [Ratio Test] Rewrite exponentials [Exponential Rule - Multiplying]: [tex]\displaystyle \lim_{n \to \infty} \bigg|\frac{x^n \cdot x}{2^n \cdot 2(n + 2)^2} \cdot \frac{2^n(n + 1)^2}{x^n} \bigg|[/tex]
- [Ratio Test] Simplify: [tex]\displaystyle \lim_{n \to \infty} \bigg| \frac{x}{2(n + 2)^2} \cdot (n + 1)^2 \bigg|[/tex]
- [Ratio Test] Multiply: [tex]\displaystyle \lim_{n \to \infty} \bigg| \frac{x(n + 1)^2}{2(n + 2)^2} \bigg|[/tex]
- [Ratio Test] Evaluate limit: [tex]\displaystyle \bigg| \frac{x}{2} \bigg| < 1[/tex]
- [Ratio Test] Isolate x: [tex]\displaystyle |x| < 2[/tex]
Our ROC is 2.
Step 3: Find IOC
Test endpoints
- [ROC] Find interval bound: [tex]\displaystyle -2 < x < 2[/tex]
x = -2
- Substitute in x [Series]: [tex]\displaystyle \sum \limit_{n = 1}^\infty \frac{(-2)^n}{2^n(n + 1)^2}[/tex]
- [Series] Rewrite [Exponential Rules - Multiplying]: [tex]\displaystyle \sum \limit_{n = 1}^\infty \frac{(-1)^n2^n}{2^n(n + 1)^2}[/tex]
- [Series] Simplify: [tex]\displaystyle \sum \limit_{n = 1}^\infty \frac{(-1)^n}{(n + 1)^2}[/tex]
Test convergence of modified series: Alternating Series Test
- [AST] Condition 1 [Limit Test]: [tex]\displaystyle \lim_{n \to \infty} \frac{1}{(n + 1)^2} = 0 \ \checkmark[/tex]
- [AST] Condition 2 [aₙ vs bₙ comparison]: [tex]\displaystyle \frac{1}{(n + 2)^2} \le \frac{1}{(n + 1)^2} \ \checkmark[/tex]
At x = -2, the series is convergent.
∴ Current IOC is -2 ≤ x < 2 or [-2, 2); 2 undetermined
x = 2
- Substitute in x [Series]: [tex]\displaystyle \sum \limit_{n = 1}^\infty \frac{2^n}{2^n(n + 1)^2}[/tex]
- [Series] Simplify: [tex]\displaystyle \sum \limit_{n = 1}^\infty \frac{1}{(n + 1)^2}[/tex]
Test convergence of modified series: Direct Comparison Test
- [DCT] Condition 1 [Define comparing series]: [tex]\displaystyle \sum \limit_{n = 1}^\infty \frac{1}{n^2}[/tex]
- [DCT] Condition 1 [Test convergence of comparing series]: [tex]\displaystyle p = 2 > 1, \ \sum \limit_{n = 1}^\infty \frac{1}{n^2} \ \text{convergent by p-series}[/tex]
- [DCT] Condition 2 [aₙ vs bₙ comparison]: [tex]\displaystyle \frac{1}{(n + 1)^2} \le \frac{1}{n^2} \ \checkmark[/tex]
At x = 2, the series is convergent.
∴ IOC for [tex]\displaystyle \sum \limit_{n = 1}^\infty \frac{x^n}{2^n(n + 1)^2}[/tex] is -2 ≤ x ≤ 2 or [-2, 2]
Topic: AP Calculus AB/BC (Calculus I/II)
Unit: Taylor Polynomials and Approximations - Power Series (BC Only)
Book: College Calculus 10e